The impacts of independent director and CEO duality on performance in the Chinese post-institutional-transition era - Lew, Yong Kyu; Yu, Jing; Park, Jeong-Yang (Wiley, 2017)
This paper investigates the influence of corporate governance on performance of modern Chinese firms. Prior studies reveal inconclusive results about the relationship between corporate governance and firm performance. Little research investigates the performance implications of board structure in the post-institutional-transition era in China. Based on agency and resource dependence theories, it examines the impacts of board composition and leadership structure on the performance of Chinese manufacturing firms that went public on the Shanghai and Shenzhen Stock Exchanges in 2010. The findings show that separating the posts of CEO and chairman promotes better performance. However, appointing a larger proportion of outside independent directors to the board insignificantly affects performance. This research provides partial support for agency theory and extended insights into corporate governance in emerging economy firms.